The epigenetics of the hypothalamic‐pituitary‐adrenal axis in fetal development. (7th March 2019) - Montenegro, Yorran Hardman A.; de Queiroga Nascimento, Denise; de Assis, Thiago Oliveira; Santos‐Lopes, Simone Silva Dos
Abstract: The hypothalamic‐pituitary‐adrenal (HPA) axis is an important hormonal mechanism of the human body and is extremely programmable during embryonic and fetal development. Analyzing its development in this period is the key to understanding in fact how vulnerabilities of congenital diseases occur and any other changes in the phenotypic and histophysiological aspects of the fetus. The environment in which the mother is exposed during the gestational period can influence this axis. Knowing this, our objective was to analyze in recent research the possible impact of epigenetic programming on the HPA axis and its consequences for fetal development. This review brought together articles from two databases: ScienceDirect and PUBMED researched based on key words such as "epigenetics, HPA axis, cardiovascular disease, and circulatory problems" where it demonstrated full relevance in experimental and scientific settings. A total of 101 articles were selected following the criteria established by the researchers. Thus, it was possible to verify that the development of the HPA axis is directly related to changes that occur in the cardiovascular system, to the cerebral growth and other systems depending on the influence that it receives in the period of fetal formation.